The best trigonometric approximations and the Kolmogorov diameters of the Besov classes of functions of many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The order estimates for the best trigonometric approximations and the Kolmogorov diameters of the classes $B^r_{p, θ}$ of functions of many variables in the space $L_q$ are obtained for certain values of the parameters $p, q$.